Cobalt-promoted fabrication of 3D carbon with a nanotube-sheet mutual support structure: scalable preparation of a high-performance anode material for Li-ion batteries. (28th November 2019) - Wu, Jiajing; Zhang, Jianghua; Ai, Yongjian; Li, Jifan; Zhang, Xinyue; Hu, Ze-Nan; Wang, He; Liang, Qionglin; Sun, Hong-bin
Abstract: Currently, the design of carbon-based composite as a high-performance anode material for lithium-ion batteries (LIBs) presents challenges for commercial application. Herein, we developed a three-dimensional carbon-based material with a nanotube-sheet mutual support structure (MS-CNTS) engineered by the catalytic effect of Co species. The present work highlights a concise 'solvent-free' synthetic method allowing for large-scale output, which is potentially available for low cost commercial use. With the readily available acetylacetonate and cobalt (II) acetylacetonate as starting chemicals, this nanostructured carbonaceous material is fabricated with aldol condensation to construct a Co-contained carbon-link network polymer precursor followed by annealing under argon. It is composed of brim-curled graphene-like carbon nanosheets and carbon nanotubes, which support each other's structures to effectively avoid agglomeration. Therefore, it enables high performance in LIBs. In spite of the trace amount of cobalt, the carbon-based MS-CNTS anode delivers a high charge capacity of 1028 mAh g −1 at 0.1 A g −1, high rate capacity of 495 mAh g −1 at 2 A g −1, and ultra-long cycling life with a very low capacity decay of 0.008% per cycle over 1000 cycles at 0.5 A g −1, accompanied by 100% Coulombic efficiency. From full cell measurements, we further confirm the considerable promise of MS-CNTS as anodes with a long cycling life.